2020
DOI: 10.1126/sciadv.abd4201
|View full text |Cite
|
Sign up to set email alerts
|

Polarization under rising inequality and economic decline

Abstract: Social and political polarization is an important source of conflict in many societies. Understanding its causes has become a priority of scholars across disciplines. We demonstrate that shifts in socialization strategies analogous to political polarization can arise as a locally beneficial response to both rising wealth inequality and economic decline. In many contexts, interaction with diverse out-groups confers benefits from innovation and exploration greater than those that arise from interacting exclusive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 55 publications
3
48
1
1
Order By: Relevance
“…To study the cultural evolution of mass political polarization, we generalize a model previously developed to study intergroup polarization and economic interactions (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the cultural evolution of mass political polarization, we generalize a model previously developed to study intergroup polarization and economic interactions (20).…”
Section: Resultsmentioning
confidence: 99%
“…The growth of intergroup antagonism has been shown to have multiple contributing factors, including economic adversity, racial animus, and a range of other socioeconomic factors (12)(13)(14)(15)(16)(17)(18)(19). Recent work focusing on the cultural evolution of polarization along identity group lines (20) has shown that a rise in economic adversity or inequality can cause polarized behavioral strategies to take hold and become entrenched in a population, even when the adverse conditions that stimulated it are reversed (21).…”
mentioning
confidence: 99%
“…The perceptions of poverty, deprivation and injustice are considered to arouse subjective feelings of frustration and anxiety that ultimately can result in more extreme political attitudes and ideologies [4]. Second, under conditions of growing poverty and greater inequality, different sub-groups of the population tend to adopt risk-averse and in-group favoring strategies while reducing out-group interactions [46]. This will facilitate the formation of the concept of "distinction", which may first push the subpopulation facing economic hardship to become polarized and then, more detrimentally result in the whole population being susceptible to a state of polarization [23].…”
Section: Connecting Income Inequality and Political Polarizationmentioning
confidence: 99%
“…Growing inequality could undermine social mobility, induce violent conflicts, and generate political tensions. At the same time, there is widespread concern that the "vicious cycle of poverty" and rising income inequality constitute an important cause of political polarization that threatens to divide and even destabilize a nation [3,46,47]. Political polarization refers to the vast and growing gap of political attitudes and identities among the public that undermine the pursuit of a common good.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation